Sacralization and limitation of the power in religious systems - O. V. Kuropatkina (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2014)
The article is devoted to the conception of power in religious systems. It deals with the functions of rulers and their responsibility to the population as well as the control mechanisms in the different religious systems. The authors conclude that in the framework of the different religious traditions boundless, at first glance, ruler / political leader’s power is limited by rigid religious rules and standards with that they must comply. Despite the fact that a political leader doesn’t have sacral status in the modern society belief in spiritual authority is preserved.